Anxiety and social media addiction on eating behaviour among university students - Lokman, Muhammad Hazim; Ibrahim, Muhamad Ariff; Mohd Nazori, Mohd Nazir; Saad, Nurulwahida; Sahid, Noor Isyah Amira (IIUM Press, 2023)
Introduction: University students may encounter a variety of stressful scenarios that may have an impact on their health and well-being as they negotiate the academic and social demands of a better education. Eating disorders are one such difficulty that may have a negative impact on both mental and physical fitness. This is due to the numerous difficulties faced by university students, which have a negative impact on how they eat. There are three types of eating behaviours can be distinguished: restrained, emotional, and external. Anxiety and addiction to social media are two elements that influence unhealthy eating behaviour. Therefore, this study is conducted to identify the relationship among anxiety, social media addiction and eating behaviour among IIUM students. Methods: This study used cross sectional design, in which samples were obtained using convenience sampling, with a total sample of 410 students. Data were collected using the General Anxiety Disorder-7 (GAD-7), Social Media Addiction Scale (SMAS) and Dutch Eating Behaviour Questionnaire (DEBQ). Results: The study reported that 53.1% experienced mild anxiety of the students. Furthermore, there is a significant association between anxiety and restrained (r= 0.165, p < 0.05), and emotional (r= 0.113, p < 0.05). However, there is no significant association between anxiety and external eating behaviour. Other than that, 64.9% of students reported that they developed a little addiction to social media. Thus, there is a significant association between social media addiction towards emotional eating behaviour (r= 0.231, p < 0.05) and external eating behaviour (r= 0.201, p < 0.05), meanwhile there is no significant association between social media addiction and restrained eating. Conclusion: Emotional eating behaviour has a weak correlation with anxiety and social media addiction.